Reducing mortality associated with opportunistic infections in Atlantic salmon Salmo salar fry using hydrogen peroxide and peracetic acid. (23rd January 2021) - DiCocco, Anna; May, Travis; Crouse, Curtis; Marancik, David; Phuntumart, Vipaporn; Ghosh, Satyaki; Beligala, Gayathri Udayangika; Redman, Natalie; Murray, Megan; Fischer, Gregory; Summerfelt, Steven; Good, Christopher
Abstract: Developing efficacious protocols for applying water disinfectants to reduce opportunistic pathogen‐associated mortalities during the Atlantic salmon Salmo salar fry stage would be highly beneficial for producers. Atlantic salmon fry (0.47 g ± 0.02) were exposed to daily stressors over four weeks while providing daily 30‐min bath treatments of 15 mg/L hydrogen peroxide (H2 O2 ), 0.2 mg/L peracetic acid (PAA) or 0.5 mg/L PAA. Survival was tracked, and skin and gill samples were collected at 2 and 4 weeks for histopathology. Moribund fish were regularly assessed via wet‐mount microscopy, with organisms resembling Saprolegnia spp. routinely observed on gills of affected fish. Tanks treated with H2 O2 had significantly ( p < 0.05) higher survival (83.7% ± 1.7) compared to controls (69.5% ± 5.2) while no significant differences were observed between either PAA treatments (76.6% ± 0.6 and 77.4% ± 3.0 survival in the 0.2 mg/L and 0.5 mg/L PAA groups, respectively) and controls. Interestingly, no significant differences were noted among treatments for waterborne Saprolegnia spp. concentrations through qPCR quantification. Lower total suspended solids (TSS) were observed in both PAA treatment groups; no other water quality differences were noted. No treatment impacts were observed through histopathology at either sampling point. These results suggest that, at the dosage and treatment regime tested, H2 O2 can be a safe and efficacious water treatment for reducing Atlantic salmon fry opportunistic infection‐associated mortality during periods of physical and environmental stress. Assessments of alternative PAA treatment regimens should also be considered in future research aimed at reducing early life‐stage mortality in Atlantic salmon.